Effects of the Fibroactívate program on physical fitness and disease impact in women with fibromyalgia: case report - Enríquez-Reyna, María Cristina (2025)
Introduction: Fibroactívate is a physical exercise program designed for women with fibromyalgia, offering three levels of training (basic, intermediate, and advanced) while considering the patient's physical fitness and the impact of the disease. Purpose: To evaluate the effects of a 12-week multicomponent intervention, based on the Fibroactívate program, on physical fitness and disease impact in women with fibromyalgia, delivered in two formats: in-person and hybrid. Methodology: Five women participated in the in-person modality (mean age 49.4 ± 5.4 years) and three in the hybrid (mean age 53.6 ± 2.1 years). The in-person group attended two supervised sessions per week and followed home-based recommendations, while the hybrid group received weekly advisory sessions and home training plans. Physical fitness was assessed using the 30-second chair stand test, arm curl test, 8-foot up-and-go test, and 6-minute walk test. Disease impact was measured using the Fibromyalgia Impact Questionnaire (FIQ). Within-group changes were analyzed using paired t-tests or Wilcoxon signed-rank tests, and between-group differences were described. Results: Both modalities showed improvements in lower and upper limb strength, cardiorespiratory capacity, and dynamic balance. A reduction in FIQ scores was observed in all participants, with a statistically significant decrease in the in-person group.  Conclusions: These findings suggest that Fibroactívate program, whether delivered in-person or in a hybrid format, may be beneficial for improving physical fitness and reducing disease impact in women with fibromyalgia.